Influence of Peripartum Supplementation of Rumen Protected Choline and Rumen Protected Fat on Blood Biochemical Profile and Postpartum Reproductive Performance in Gir Cows - Chavda, Miteshkumar R.; Savsani, Harish H.; Karangiya, Vijay K.; Belim, Saman Y.; Kansagara, Yash G.; Javia, Bhavesh B.; Kalariya, Vinay A. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study was conducted on 24 advanced pregnant Gir cows in their first to third lactation to evaluate the effects of supplementing  rumen protected choline (RPC) and rumen protected fat (RPF) alone or in combination on various blood biochemical parameters and  postpartum reproductive performance. The cows were divided into four equal treatment groups (n=6 each), viz., T1 (control), T2 (RPC),  T3 (RPF) and T4 (RPC and RPF), based on their parity, body weight and previous lactation yield. In T1 group, cows were fed with basal diet  to meet their nutrient requirement as per ICAR (2013) feeding standards. In T2 group, cows were supplemented with RPC @ 45 g/day, in  T3 with RPF @ 80 g/d and in T4 with RPC @ 45 g/day + RPF @ 80 g/d along with basal diet of T1 starting from 30 days before expected  date of calving to 60 days postpartum and blood samples were collected at monthly intervals. Supplementation of RPC and RPF alone  or in combination had no significant effect on plasma BUN, cholesterol, TAG, VLDL, NEFA and BHBA levels. Days to first observed heat  were reduced significantly (p
Keywords: Gir cows; Peripartum metabolic profile; Postpartum fertility; Rumen protected choline; Rumen protected fat